That is the final answer to this question
42765
Answer:
= One-half more than three-fourths of a number
= Three-fourths minus one-half of a number
= three-fourths minus the sum of a number and one-half
Step-by-step explanation:
Suppose x be an unknown number.
∵ 3/4th of a number = ![\frac{3}{4}x](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B4%7Dx)
= One-half more than three-fourths of a number
Now, half of a number = ![\frac{1}{2}x](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7Dx)
= Three-fourths minus one-half of a number
Sum of a number and one-half = ![x+\frac{1}{2}](https://tex.z-dn.net/?f=x%2B%5Cfrac%7B1%7D%7B2%7D)
= three-fourths minus the sum of a number and one-half
Answer:
the answer is 80
Step-by-step explanation:
hope we can be friends
can i please get brainliest
3 = -(-y + 6)
First, simplify brackets. / Your problem should look like: 3 = y - 6
Second, add 6 to both sides. / Your problem should look like: 3 + 6 = y
Third, simplify 3 + 6 to 9. / Your problem should look like: 9 = y
Fourth, switch sides. / Your problem should look like: y = 9
The answer is D) 9.
Answer:
After the 35 gel pens??
Step-by-step explanation: